The Impact of Subjective Social Position on Public Evaluations of Police. (30th March 2021) - Martinez‐Ebers, Valerie; Branton, Regina; Calfano, Brian
Abstract : Objective: We examine factors that explain differences in assessment of police performance among whites, African Americans, Asians, and Latinos, and utilize a subjective social position framework to better understand variation in poor police evaluations. The framework combines previously disparate explanations in the literature. Method: Logit models assess 2016 Collaborative Multiracial Post‐Election Survey data augmented by Census, FBI crime statistics, and Mapping Police Violence Project data to assess respondents' police performance evaluations. Results: Feelings of marginalization, negative perceptions of local context, and involuntary contact with police are more important for predicting poor evaluations of police than objective contextual conditions, including police‐initiated violence. Conclusion: Despite variation across racial and ethnic groups, the subjective social position of individuals goes a long way in explaining individuals' evaluation of police performance. However, African Americans are clearly more critical of law enforcement than other minorities, with at least some of this disparity explained by differences in subjective social position.